Effects of Grid Voltage and Load Unbalances on the Efficiency of a Hybrid Distribution Transformer - Alvaro Carreno; Mariusz Malinowski; Marcelo A. Perez; Jingyu Ding (IEEE Open Journal of the Industrial Electronics Society)
The hybrid distribution transformer (HDT) has been proposed as a solution to cope with the low short-circuit capability of solid-state transformers. Among the available HDT configurations, the one that connects a series/parallel converter on the primary/secondary side can be highlighted. This configuration improves the voltage and current waveforms on the transformer and regulates the voltage supplied to the ac microgrid. Nonetheless, this HDT suffers from a circulating active power flow (CAPF), affecting its efficiency. Moreover, during the unbalanced operation of the HDT, an additional CAPF component exists. Depending on the grid and load conditions and whether the parallel converter compensates for the load unbalances, the CAPF can either increase or decrease. Although the CAPF can be eliminated by employing the dc port of the HDT, it is not always possible to extract energy from it. This work contributes with the analysis of the operation of an HDT under an unbalanced grid voltage and load, along with an extended CAPF model that considers the losses of the HDT. The effect of the unbalanced components on the CAPF is analyzed, and the conditions in which the CAPF is minimized are obtained. Nonetheless, in most scenarios, a minimum CAPF does not coincide with the maximum efficiency of the HDT. Therefore, the conditions for achieving maximum efficiency are also determined. A simpler suboptimal condition is obtained due to the complexity of requiring precise parameters and operating conditions of the HDT. Moreover, the suboptimal condition allows for improving the power quality of the HDT. Therefore, a certain amount of CAPF is desired to operate the HDT properly.